Investigating the Success and the Advantages of Using ERP System in KSA Context - Abdel-Haq, M. S.; Chatti, H.; Asfoura, E. (Engineering, Technology & Applied Science Research, 2018)
Enterprise resource planning (ERP) is an important innovation, affecting the business world by generating improvements both tangible and intangible in large companies and small and medium enterprises (SME). This study focuses on the determinants of success and the advantages of the adoption of this technology. To address these points, a comprehensive literature survey was carried out in order to formulate an original research model for ERP success evaluation and provide a prospect for IT infrastructure and integration. The model, thus suggested and taken within the Kingdom of Saudi Arabia (KSA) context, examines in a systematic approach the relation between the ERP acceptance determinants, the effects of the process of ERP systems diffusion, and the impacts expected on organizational performance. Obtained results underline two key determinants of ERP projects success: First, the preponderance of information control and the improvement in the use of competences. The second factor is the quality of team projects, the definition of team’s mission, training, business processes reengineering, user acceptance, top management support and the selection of the ERP solution.